A Variabilidade da precipitação no Rio Grande do Sul e sua relação com o Índice de Oscilação Antártica - Garcia, Maria Arita Madruga (2011)
This research aims to analyze the monthly variations of rainfall in Rio Grande do Sul (RS) relating to monthly changes in the average thickness of the troposphere (700mb) at the bottom of the Southern Hemisphere, which is centered in the region of Antarctica. Monthly anomalies of atmospheric thickness have been represented by principal oscillation pattern that is called the Arctic Oscillation Index. This study is important because RS has played an important role in national agricultural production, and the variable rainfall has been identified as a key role in the productivity of different regional cultures. During the study, monthly rainfall data from 32 meteorological stations in RS has been used, which has been correlated with the Arctic Oscillation Index. The Arctic Oscillation Index has been obtained directly from Climate Prediction Center and the study period has been from 1979 to 2008 and, the correlations between the monthly rainfalls have been tested considering the time lags of index 0, -1, -2, -3 months. The results of the climatology have showed that rainfall in these last three decades have presented patterns and distributed monthly throughout the year and lower values to the south and higher to the north and northwest. The largest temporal gradient in RS has occurred between the months of October and November, with their maximum and minimum respectively. The Antarctic Oscillation Index has had its greatest variations in the middle of winter and the smallest variations in late summer. The more significant correlations of rainfall in RS and the index have been mostly reversed (by the way the index is built). The highest correlation has been between the rainfall for the month of May and the index also the month of May especially in the northern half of the RS. In the southern half of RS, the changes in the index in March have shown a higher correlation considering rainfall in March and April. The highest correlations in the northwestern part of RS have been happening between the rainfall of November and November Index and the central region of RS has been showing significant correlations in December with the index in November. Among the best results (the highest correlations) it has been highlighted those correlations of the months of March, April and May. From the average rate for the quarter, the extremes of the index have been identified and climatologies of rainfall have been calculated for the two groups (six negative extreme cases and six positive extreme cases). During the negative rainfall period, the index of quarterly rainfall has been exceeding by up to 50% the positive rainfall period, mainly in the south and west of RS. The negative period has been associated to the intensification of high polar consequently it has also been associated to the intensification of the polar jet, thus the most organized cold fronts pass through the RS, while in positive periods the weakening of the high polar and changes in zonal flow of the subtropical jet have been happening, reducing the intensity of cold fronts.